Analysis on English Textbook For Third-Grade In Senior High School - Ratu Amelia Awal (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims to find out whether the textbook is eligible for students based on the National Education Standards Agency (BSNP), to find out the benefits of textbook used by teacher in third grade, and to find out the difficulties faced by teacher in using textbook. This research used a document study method with descriptive analysis and a qualitative approach. This research used two instruments. First, this research used four indicators of textbook eligibility based on the National Education Standards Agency (BSNP). Second, using teacher interview techniques to determine the benefits of textbooks used for third-grade students and to determine the difficulties of teachers face in using textbooks in learning. The results of the research indicate that the English textbook for grade XII SMA (Ministry of Education and Culture of the Republic of Indonesia) Revised Edition 2018 is included in the category of eligibility in terms of Content eligible because the suitability of the material description with the core competencies (KI) and basic competencies (KD) contained in the curriculum. Presentation eligibility because the presentation technique is under the indicators. This book also the Language Eligibility because the language used is appropriate and easy to understand for students and teachers, and Graphic Eligibility has been appropriate because it has met the indicators of BSNP. This textbook is very useful for teachers and students because it guides teachers in delivering material and is also a source of learning for students. In addition, the material presented in this textbook is also under the needs for students, and the language used is quite good and easy to understand. In addition, the material presented in this textbook is under competency standards and basic competencies. Meanwhile, the challenges faced by teachers in using this textbook are that it is not equipped with listening materials, and it is also limited to school libraries.